Bolivia : Poverty Diagnostic 2000 - World Bank (Washington, DC, 2013)
The report presents a diagnostic of poverty, human development, and access to social infrastructure in Bolivia, based on analytical work, to serve as an input for the Poverty Reduction Strategy Paper (PRSP). Findings suggest that poverty affects half of the population in large cities, two thirds in other urban areas, and eighty percent in rural areas. Nonetheless, there is seemingly a recent decrease in inequality, although this does not imply a long-term trend. The complex determinants of poverty, are also increased by the fact of being from an indigenous population, and of having a household head unemployed, underemployed, and/or female. Since poverty decreases with education, and employment in non-agricultural occupations, and geography affects poverty, migration becomes a poverty-reducing tool. A qualitative study of farmers in the Altiplano suggest decreased rural productivity, intensified by climatic, demographic, and environmental pressures, with little gain from most development projects. Hence, progress in non-monetary indicators show that while unsatisfied basic needs fell significantly from 1976 to 2001, the gains were mainly achieved in urban areas, and needs remain large in rural areas. It is suggested that this progress in basic needs measures, lies in the increased social spending, but the scope for reducing monetary poverty, lies in the accessibility to public infrastructure services, in reducing violence, and gender issues. But the impact of growth needs further understanding, with improvements in productivity and competitiveness, enlarged by improvements in education, health, and nutrition, where the poor may benefit more than the non-poor from the expansion of these services.